P3HT:PCBM blend films phase diagram on the base of variable-temperature spectroscopic ellipsometry - Hajduk, Barbara; Bednarski, Henryk; Jarząbek, Bożena; Janeczek, Henryk; Nitschke, Paweł (Beilstein Journal of Nanotechnology, 2018)
In this work we present an in-depth study of the how the composition of poly(3-hexylthiophene) (P3HT):[6,6]-phenyl-C61-butyric acid methyl ester (PCBM) blend films influences their phase transitions using variable-temperature spectroscopic ellipsometry. We demonstrate that this non-destructive method is a very sensitive optical technique to investigate the phase transitions and to determine the glass transition temperatures and melting crystallization points of the P3HT:PCBM blend films. By analyzing the influence of the temperature T on the raw ellipsometric data, we have identified a high sensitivity of the ellipsometric angle Δ at a wavelength of 280 nm to temperature changes. Characteristic temperatures determined from the slope changes of the Δ(T) plot appeared to be very good guess values for the phase transition temperatures.
Keywords: non-linear optics; organic semiconductors; spectroscopic ellipsometry; theoretical modeling; thin films